Effect of Chelated Mineral Mixture on Blood Biochemistry, Hormone and Mineral Status in Repeat Breeder Buffaloes in Tribal Areas of Dahod District in Gujarat, India - Joshi, PM; Patel, DC; Patel, PD (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
An on-farm trial for 90 days was conducted at four tribal villages to assess the effect of chelated mineral mixture (CMM) supplementationon blood biochemistry as well as hormonal and mineral status, nutrient intake and reproductive performance of the repeat breederbuffaloes (n = 24). The animals selected were randomly divided into two groups of 12 animals each. The group T1 was control group(farmer’s feeding schedule), and T2 treatment group (T1 + CMM @ 50 g/animal/day). Blood collection was done at 0, 45 and 90 days ofthe experiment from both the groups for assessment of blood biochemical, hormonal and mineral status of the animals. Average DM,DCP and TDN intake in repeat breeder buffaloes calculated as per information collected from farmers were statistically similar amongboth the groups and were as per ICAR requirements of animals. Results revealed significant (p
Keywords: Buffalo; Mineral supplementation; Repeat breeder; Macro-micro minerals,; Reproductive status; Cost-benefit ratio